The Effect of PISA-Based Mathematical Literacy on Students’ Mathematical Problem-Solving Ability in Terms of Prior Mathematical Knowledge - Mar Athul Wazithah T; Norma Nasir (International Journal of Technology and Education Research, 2026)
This study aims to examine the effect of PISA-based mathematical literacy on students’ mathematical problem-solving ability in terms of prior mathematical knowledge. This research employed a quantitative approach with a correlational design. The sample consisted of 60 students enrolled in a Basic Statistics course in the Actuarial Science study program at Universitas Negeri Makassar. The data were collected through tests of mathematical literacy, problem-solving ability, and prior mathematical knowledge. Data were analyzed using multiple regression with an interaction term. The results show that PISA-based mathematical literacy has a significant positive effect on students’ problem-solving ability (β = 0.528; Sig. = 0.000 < 0.05). Prior mathematical knowledge also has a significant effect (β = 0.347; Sig. = 0.000 < 0.05). Furthermore, there is a significant interaction between mathematical literacy and prior knowledge (β = 0.015; Sig. = 0.015 < 0.05), indicating that the effect of mathematical literacy is stronger among students with higher prior knowledge. These findings suggest that integrating PISA-based tasks and considering students’ prior knowledge are essential for improving mathematical problem-solving ability.